Prevalence of Anaemia among Rural Women Population of Paschim Medinipur, West Bengal, India - Maiti, S; Ali, KM; Ghosh, A; Ghosh, D; Paul, S (Nepal Journal of Medical Sciences, 2013)
Background: Anaemia is a common health problem among women throughout the world and vast majority of this burden occurs in developing countries. In the present study, an attempt has been made to gauge the prevalence of anaemia among adult women residing in five rural blocks of Paschim Medinipur, West Bengal, India. Therefore, associations between haemoglobin concentration and anthropometric data were evaluated. Methods: The study was confined to the non-pregnant women of age group of 21-50 years. A total of 368 women were participated in the present study. The estimation of anaemia was undertaken using the standard procedure and anthropometric measurements were collected. Anaemia was classified as per the World Health Organisation (WHO) grading criteria. Results: The overall prevalence of anaemia among women was 70.1%. The majority 205 (55.7%) demonstrated moderate anaemia while mild anaemia was recorded in 53 (14.4%) and none of the subject had severe anaemia. Lower body mass index was associated with higher prevalence of anaemia. Conclusion: This study revealed that anaemia is present at considerable levels among adult women in our study area which provide intensive approaches are required to combat the anaemia in this population. Nepal Journal of Medical Sciences | Volume 02 | Number 01 | Jan-Jun 2013 | Page 9-12 DOI: http://dx.doi.org/10.3126/njms.v2i1.7644